Development of Video Tutorial Media in the Computer Networking Course at Indonesia Christian University Toraja - Anna Pertiwi; Enos Lolang (Universitas Muhammadiyah Enrekang, 2023)
This research analyzes the problem of lack of literacy and references for practicum material that students can use to make it easier for them in practicum, making students overwhelmed and having difficulty completing the project assignments given. To answer the challenges of the digitalization 5.0 era and make things easier for students, innovations are needed in learning Computer Networks courses, the innovation of which is in the form of video tutorial media which can motivate students to have more fun learning and make it easier for students to absorb knowledge and skills in the field of Computer Networks. This research method uses a type of research and development (R & D) Instructional Development Institute (IDI) development model using qualitative data analysis. This research will be carried out at the Indonesian Christian University of Toraja with students from the Educational Technology Study Program as research subjects. The results of the development in this research are video tutorial media products with a duration of ± 7 minutes which are packaged in the form of teaching materials that are ready to be used. The validation level of the video tutorial media developed is based on material and media experts, is in the valid category, and is suitable for testing. Keywords: Computer Networks, Video Tutorials, Educational Technology